Ameriška mladinska proza od obdobja po drugi svetovni vojni do konca šestdesetih let - Mazi-Leskovar, Darja (Otrok in knjiga, 1999)
In the period after second world war American children's literature on the one hand continued the tradition of the prewar era, while on the other hand it started showing openess for new styles, approaches and themes. At the same time some traditional genres got either new forms or original points of view. First person narrative attracked the young readres who were taken more and more seriously also as far as their personal experience is concerned (Elizabeth Borton de Trevino's I Juan de Pareja - 1965). Incorporation of the black experience started with the books written by whites, as Dorothy Sterling's Mary Jane (1959) and William H. Armstrong's Sounder (1969), and taken over by more and more Afro-American writers in this period represented particularly by Virginia Hamilton (The House of Dies Drear - 1968, Time-ago Tales - 1969). New forms of animal fantasies written by E. B. White (Stuart Little - 1945, Charlotte's Web - 1952 and The Trumpet of the Swan - 1970) and Russel Hoban (Bedtime Hoban (Bedtime for Frances - 1960) were enjoyed by children of various agegroups. Older readers were offered science fiction books by Madeleine L'Engle (A Wrinkle in Time - 1962). It is the period of the establishment of the Hans Christian Andersen Award and the first American children's writer to be honored was Meidert De Jong. The author attracted the reading public with Shadrach in 1953 and was awarded the worldwide recognition in 1962. Even if the richness of the production in the field of children's literature is due to many reasons, the more founding of the Laura Ingalls Wilder Award proves that children's literature met with a new recognition on the national level as well.
Keywords: mladinska književnost; young adult literature; American literature; ameriška književnost; prose; proza; zgodovinski pregledi